Public virtue, private ambition : the quiet rise of entrepreneurial women in New Zealand’s private hospitals 1890-1935 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University, Albany, New Zealand - Quinn, Ann-Marie (Massey University, 2023)
Historians say that nursing in New Zealand became professionalised while riding the first wave of feminism in the late nineteenth century. This was supposedly achieved by preserving the doctor-nurse hierarchy, thus presenting no threat to the medical man’s status or prejudices. Social norms of the time meant nurses generally worked until they were married but for those who remained single or who became single through death or divorce, it offered a career path and an opportunity for independence in a feminine and socially acceptable vocation. By the early twentieth century, New Zealand’s health service had evolved into a two-tier system of Government-owned public hospitals in most of the country’s major towns supported by a network of private hospitals predominantly owned by nurses and midwives. The strong legislative framework introduced between 1901 and 1906 requiring nurses, midwives and their hospitals to be registered, licensed and regularly monitored could potentially have put a straight jacket around the industry. Instead it required women to be politically, financially and vocationally savvy to meet the exacting standards of the evolving regulatory environment. This proved to be fertile ground on which many women were able to succeed. This thesis argues that the creation of this significant social and commercial space dominated by women breaks with the traditional idea of nurses as carers and handmaidens to the doctors and positions them as enterprising, independent businesswomen with authority and agency within their hospitals and a new power dynamic between themselves and the medical community.
Figure 2 was removed for copyright reasons, but is accessible at https://www.aucklandmuseum.com/collections-research/collections/record/am_library-photography-2126?k=PH-NEG-H291&ordinal=0. Figures 3 & 6 are ©The Coromandel Heritage Trust, but are reproduced with permission. Figure 4 is reproduced under a Creative Commons Attribution-NonCommercial 4.0 International (CC BY-NC 4.0) license.
Keywords: 430320 New Zealand history